A Comparative Study of Learning Related Emotions among Male and Female Health Field University Students in Saudi Arabia (European Journal of Teaching and Education, 2020)
The present study investigates the level of learning-related emotions as well as to looks at the differences between female and male undergraduate health tack students for learning-related emotions levels. A self-reported measure of learning-related emotions was collected from 120 university students from East Saudi Arabia, which were selected by stratified random sampling. The results indicated that students’ having good feelings towards their learning at the university. When comparing students’ gender groups, the results also showed insignificant differences between males and females’ students on their emotions towards their learning at the university. Finally, the study provided recommendations for further research and educational practices.